Ways to Inhabit the Deliberative-Aspirational Point of View: Practical Reason and Objective Goods. (21st September 2022) - Rodriguez-Blanco, Veronica
Abstract: In "Practical Reason's Foundations" John Finnis expands and refines his view on the relationship between objective goods and practical reason. In this paper Finnis rejects the Humean conception which denies the possibility of practical reason, or at least presents an emaciated version of it. For Hume, desires just happen to us and there is no interaction between desires and beliefs. The Humean and neo-Humean positions, Finnis rightly tells us, have a powerful influence on how we understand practical reason, including our interpretation of Aristotle's conception of practical reason. I will call this the "bifurcation" thesis. Following Finnis's conception of practical reason and his rejection of a bifurcation between reasons and desires, and between intellectual virtues and virtues of character, I advance an Aristotelian-inspired model of deliberation and practical reason that is narrow and immersed. It recognizes the difficulty of understanding the Aristotelian analogies of practical reason as if it were both a craft and theoretical reasoning to illuminate and demonstrate the existence of practical reason. However, I also argue that this narrow or immersed model is in continuity with a deliberative-aspirational perspective that we are able to inhabit. We explain how reflection without losing immersion is possible and explain how we can move in the direction of practical reason that guides actions and makes possible the realization of objective goods in our lives.